Plexin-B1, glycodelin and MMP7 expression in the human fallopian tube and in the endometrium - Goldman Shlomit; Romano Shabtai; Amir Michal; Shalev Eliezer (BMC, 2009)
Abstract Background To study the expression of Plexin-B1, Glycodelin, and MMP7 during the menstrual cycle in the endometrium and in the fallopian tube. Methods The research included women undergoing hysterectomy, tubal sterilization or salpingo-oophoerectomy. Total RNA from endometrial and fallopian tube tissues was extracted using a total RNA isolation kit. Semi-quantitative RT-PCR was performed to examine mRNA relative expression. Results Plexin-B1 expression in the endometrium was significantly higher on days 19 - 23 compared to days 12 - 14 (1.166 +/- 0.42 versus 0.523 +/- 0.299), P < 0.005. In the fallopian tube the level of plexin-B1 did not change significantly throughout the menstrual cycle. Glycodelin expression was significantly higher on days 19 - 23 compared with days 12-14, both in the endometrium (0.819 +/- 0.564 versus 0.072 +/- 0.343, P < 0.05) and the fallopian tube (0.796 +/- 0.196 versus 0.329 +/- 0.398, P < 0.05). Although the level of MMP7 secretion was the highest in the secretory phase the difference from the proliferative phase did not reach statistical significance, neither in the endometrium nor in the fallopian tube. This could result from a lack of power. Conclusions In the endometrium, both Glycodelin and Plexin-B1 are exhibiting a cyclic pattern suggesting a possible steroid regulation and a role in endometrial receptivity.